Phytotherapy as the part of the complex treatment of lower urinary tract diseases - G. V. Bachurin (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
The use of phytotherapy in the treatment of urinary tract diseases has been known for a long time. But at present it has become widely used and got scientific justification for urological pathology, particularly in the treatment of prostatitis.